Unveiling urban biodiversity: An interdisciplinary hands-on project that catalyzes awareness - Ana Paula Oliveira; António Bajanca; Ana Paramés (Environmental and Sustainability Indicators)
Urbanization, a global phenomenon, has significantly transformed ecosystems, often leading to the loss of biodiversity. Despite these challenges, urban green spaces (UGS) continue to serve as essential refuges for diverse flora and fauna within cities. This study presents an interdisciplinary, hands-on project implemented at the Portuguese Higher Institute of Education and Sciences (ISEC Lisboa), employing a Project-Based Learning (PBL) approach to explore and enhance urban biodiversity awareness. Involving 75 students from ISEC Lisboa, the project effectively demonstrated the efficacy of the PBL methodology in promoting student engagement and yielding concrete outcomes, such as a comprehensive survey documenting 71 species (39 fauna and 32 flora). To amplify the project's impact, the findings were disseminated through a well-structured communication strategy, that actively involved the students, including an on-campus exhibition and the publication of both a book and an e-publication. The participation of local schools and the recognition of the project through an environmental awareness award underscored its success in connecting academic research with community education, showcasing its potential as a model for similar urban initiatives. This study highlights the significant role of UGS as powerful educational resources that foster a deeper understanding of ecological principles and promote sustainable urban living. Additionally, it emphasizes the crucial responsibility of higher education institutions in advancing biodiversity conservation, habitat protection, and advancing broader ecological priorities to support the development of resilient and sustainable urban environments.